Optimize width of navigational channels and ships turning basins in ports - Paulauskas, Vytautas; Paulauskas, Donatas; Plačienė, Birutė; Lukauskas, Valdas (Transport, 2016)
A number of ports are located close to cities or have other limitations on approaching areas of water. The optimization of the port and the use of possible areas of water are linked with the maximum number of the ships that could enter the port. The main factor considered in the presented study is the potential possibilities of water areas used for the ships entering the port as well as manoeuvring, turning, mooring and unmooring operations performed by the largest ships.First published online: 13 Jul 2015